PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP CORPORATE SOCIAL RESPONSIBILITYDISCLOSURE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Dewi, Sukmawati Safitri (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This main aims of this studyis to test whether the company characteristics consist of size, profitability, leverage, management ownership, and the number of the board of commissioners.The results of this study show that: (1) size have an influence to the corporate social responsibility disclosure, (2) profitability have no influence to the corporate social responsibility disclosure, (3) leverage have no influence to the corporate social responsibility disclosure, (4) management ownership have an influence to the corporate social responsibility disclosure, dan (5) the number of the board of commissioners have an influence to the corporate social responsibility disclosure.Keywords: Size, Profitability, Leverage, Management Ownership, Size of the Board of Commissioners, Corporate Social Responsibility Disclosure (CSRD).